1996
DOI: 10.1111/j.0022-3646.1996.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

CORRELATED BIOCHEMICAL AND ULTRASTRUCTURAL CHANGES IN NITROGEN‐STARVED EUGLENA GRACILIS1

Abstract: Growth of Euglena gracilis Z Pringsheim under photoheterotrophic conditions in a nitrogen‐deprived medium resulted in progressive loss of chloroplastic material until total bleaching of the cells occurred. Biochemical analysis and ultrastructural observation of the first stages of the starvation process demonstrated an early lag phase (from 0 to 9 h) in which cells increased in size, followed by a period of cell division, apparently supported by the mobilization of some chloroplastic proteins such as the photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…Although numerous authors have dealt with plastid development and division in the euglenophytes, they have all used E. gracilis as their study organism (Cook et al 1976, Pelligrini 1980, Ehara et al 1990, García‐Ferris et al 1996). Ours is the first report of plastid division and pyrenoid development in euglenophyte taxa other than E. gracilis , but it appears that many of the phenomena reported for E. gracilis are maintained within euglenophytes with similar type plastids.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous authors have dealt with plastid development and division in the euglenophytes, they have all used E. gracilis as their study organism (Cook et al 1976, Pelligrini 1980, Ehara et al 1990, García‐Ferris et al 1996). Ours is the first report of plastid division and pyrenoid development in euglenophyte taxa other than E. gracilis , but it appears that many of the phenomena reported for E. gracilis are maintained within euglenophytes with similar type plastids.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited growth is sometimes possible during periods of nutrient shortage. A proposed mechanism for this phenomenon under nitrogen‐limiting conditions was suggested by García‐Ferris and coworkers using Euglena gracilis as a model. These researchers showed that E. gracilis was able to resume growth after being transferred to a N‐free medium for 15 h (roughly one generation); this resumed growth was feasible due to the reallocation of chloroplastic proteins, such as the photosynthetic CO 2 ‐fixing enzyme ribulose‐1,5‐bisphosphate carboxylase/oxygenase (RuBisCO).…”
Section: Lipidsmentioning
confidence: 99%
“…N-deprivation, by contrast, profoundly affects the chloroplast structure, and causes a time-dependent loss of chloroplast enzymes. In a carbon-rich cellular medium like that of N-starved cells, it was observed that ribulose-1,5-bisphosphate carboxylase/oxygenase and other chloroplast material can serve as an N source for synthesis of other N-compounds (Garcia-Ferris et al 1996).…”
Section: Introductionmentioning
confidence: 99%